Evolution of a concept with enzymatic debridement and autologous in situ cell and platelet-rich fibrin therapy (BroKerF). (January 2022) - Waldner, Matthias; Ismail, Tarek; Lunger, Alexander; Klein, Holger J; Schweizer, Riccardo; Alan, Oramary; Breckwoldt, Tabea; Giovanoli, Pietro; Plock, Jan A
Background: Deep partial-thickness burns are traditionally treated by tangential excision and split thickness skin graft (STSG) coverage. STSGs create donor site morbidity and increase the wound surface in burn patients. Herein, we present a novel concept consisting of enzymatic debridement of deep partial-thickness burns followed by co-delivery of autologous keratinocyte suspension and plated-rich fibrin (PRF) or fibrin glue. Material and methods: In a retrospective case study, patients with deep partial-thickness burns treated with enzymatic debridement and autologous cell therapy combined with PRF or fibrin glue (BroKerF) between 2017 and 2018 were analysed. BroKerF was applied to up to 15% total body surface area (TBSA); larger injuries were combined with surgical excision and skin grafting. Exclusion criteria were age <18 or >70 years, I°, IIa°-only, III° burns and loss of follow-up. Results: A total of 20 patients with burn injuries of 16.8% ± 10.3% TBSA and mean Abbreviated Burn Severity Score 5.45 ± 1.8 were identified. Of the patients, 65% (n = 13) were treated with PRF, while 35% (n = 7) were treated with fibrin glue. The mean area treated with BroKerF was 7.5% ± 0.05% TBSA, mean time to full epithelialization was 21.06 ± 9.2 days and mean hospitalization time was 24.7 ± 14.4 days. Of the patients, 35% (n = 7) needed additional STSG, 43% (n = 3) of whom had biopsy-proven wound infections. Conclusion: BroKerF is an innovative treatment strategy, which, in our opinion, will show its efficacy when higher standardization is achieved. The combination of selective debridement and autologous skin cells in a fibrin matrix combines regenerative measures for burn treatment. Lay Summary: Patients suffering from large burn wounds often require the use of large skin grafts to bring burned areas to heal. Before the application of skin grafts, the burned skin must be removed either by surgery or using enzymatic agents. In this article, we describe a method where small areas of skin are taken and skin cells are extracted and sprayed on wound areas that were treated with an enzymatic agent. The cells are held in place by a substance extracted from patients' blood (PRF) that is sprayed on the wound together with the skin cells. We believe this technique can be helpful to reduce the need of skin grafts in burned patients and improve the healing process.